Construction of carbon budget balance index and its application in the lake area - Li, Shuoshuo; Liu, Yaobin; Wei, Guoen; Sevegnani, Fábio; Deng, Weifeng (Frontiers in Ecology and Evolution, 2023)
The imbalance of the carbon cycle in terrestrial ecosystems exacerbates global warming. Identifying the spatial–temporal characteristics and drivers of the carbon budget is important for the effective management of complex ecosystems and the achievement of the United Nations Sustainable Development Goals. Based on the complex ecosystem theory, this article constructs two carbon indicators, carbon carrying capacity–carbon footprint matching degree (Carbon-MD), and carbon carrying capacity–carbon footprint coupling coordination degree (Carbon-CCD). Taking a typical lake region—urban agglomeration around Poyang Lake as an example, the spatial–temporal characteristics and driving factors of the carbon budget from 2000 to 2020 are revealed by GIS technology and geographically–temporally weighted regression model. The results show that there is a significant spatial and temporal variability of carbon budget in Poyang Lake city agglomerations from 2000 to 2020, the Carbon-MD shows a gradually decreasing trend, and the Carbon-CCD shows a gradually increasing characteristic from moderate disorder to basic coordination development. From the spatial pattern, the Carbon-MD of the study area showed an increasing character from the core area to the peripheral area of the lake, and the low-value area of Carbon-MD shows the trend of spreading from point to surface and the Carbon-CCD changes from scattered to group type. In addition, land use type always has a significant effect on the carbon budget, while there is a spatial and temporal heterogeneity in the effects of natural and socioeconomic factors on the carbon budget. The research results show that it is reasonable and scientific to construct carbon budget indicators from the perspective of matching supply and demand and coupling and coordination, which provides a quantitative carbon budget analysis tool for local policymakers.